Regulator of G-protein signalling 3 redirects prototypical Gi-coupled receptors from Rac1 to RhoA activation - Vogt, Andreas; Lutz, Susanne; Rümenapp, Ulrich; Han, Li; Jakobs, Karl-Heinz; Schmidt, Martina; Wieland, Thomas (Cellular signalling, 2007)
The small GTPases, Rac1 and RhoA, are pivotal regulators of several essential, but distinct cellular processes. Numerous G-protein-coupled receptors signal to these GTPases, but with different specificities. Specifically, Gi-coupled receptors (GiPCRs) are generally believed to activate Rac1, but not RhoA, a process involving Gβγ-dimers and phosphatidylinositol 3-kinase (PI3K). Here we show that, depending on the expression level of the 519 amino acid isoform of regulator of G-protein signalling 3 (RGS3L), prototypical GiPCRs, like M2 muscarinic, A1 adenosine, and α2-adrenergic receptors, activate either Rac1 or RhoA in human embryonic kidney cells and neonatal rat cardiomyocyte-derived H10 cells. The switch from Rac1 to RhoA activation in H10 cells was controlled by fibroblast growth factor-2 (FGF-2), lowering the expression of RGS3L. Activation of both, Rac1 and RhoA, seen at low and high expression levels of RGS3L, respectively, was sensitive to pertussis toxin and the PI3K inhibitor LY294002 and mediated by Gβγ-dimers. We conclude that RGS3L functions as a molecular switch, redirecting GiPCRs via Gβγ-dimers and PI3K from Rac1 to RhoA activation. Considering the essential roles of Rac1 and RhoA in many signalling pathways, this additional function of RGS3L indicates a specific role of this protein in cellular signalling networks.